LIFE CYCLE ASSESSMENT OF WET NOODLES PRODUCTS AT MIE CEPET IBU RUBIYEM MICRO SMALL MEDIUM ENTERPRISE (MSME) BANDAR LAMPUNG CITY - Aditya Wahyu Nugraha; Fia Fitriawan; Untung Trimo Laksono (Jurnal Teknologi Industri Pertanian, 2025)
Wet noodles are a type of noodle that undergoes a boiling process before being marketed. Activities in the wet noodle production process can produce waste and emissions that have the potential to cause environmental impacts. The resulting environmental impacts include greenhouse gas (GHG), acidification, and eutrophication. The amount of environmental impact produced can be determined through the life cycle assessment (LCA) method. This research aimed to measure the potential impact of GHG emissions, acidification, and eutrophication, and provide recommendations for alternative improvements to reduce the resulting emissions. The scope used was gate-to-gate and the functional unit was1 kg of wet noodles. The environmental impact analysis that has been carried out showed that the amount of GHG, acidification, and eutrophication were 4.72x10-1 kgCO2eq, 1.82 x 10-5 kgSO2eq, and 5.97 x 10-3 kgPO43-eq, respectively. Recommendations for alternative improvements that can be made are (1) Substitution for the use of renewable energy, namely off-grid solar power plants (SPE), which can reduce GHG emissions by 0.19%, acidification by 63.1%, and eutrophication 79.5%. (2) The use of electric vehicles (EV) as the main energy source from off-grid solar power plants can reduce GHG emissions by 0.02% and acidification by 3.64%. (3) Converting wastewater into liquid organic fertilizer (LF) can reduce GHG emissions by 78.4% and eutrophication by 1.12%, and (4) Selling solid waste (SSW) to livestock feed can reduce GHG emissions by 19.2% in all processes. Keywords: acidification, eutrophication, Greenhouse gases (GHG), Life Cycle Assessment (LCA), wet noodles